What do we know about the impacts of the next El Niño on agrifood systems? - Koo, Jawoo; Anderson, Weston (CGIAR, 2023)
As of June 2023, there is a consensus among the climate science community and prediction centers that the El Niño-Southern Oscillation (ENSO) of the upcoming boreal winter season (November 2023 – February 2024) will transition to an El Niño event, ending the recent three-year La Niña 1. El Niño naturally re-occurs every 2 to 7 years, and its cycle typically lasts 9 to 12 months, starting with a slow onset during the boreal (Northern Hemisphere) spring season (March-June), peak intensity during the late fall or winter (November-February), followed by weakening during the spring or early summer (March-June). Its unique slow onset, periodic pattern, and lead-times of prediction (from a few months to a year) make it possible to design anticipatory policies and prepare emergency responses a few months in advance.